Product development : from invention to innovation - Raja Ahmad Effendi, Raja Ahmad Azmeer; Baharuddin, Nasir (Universiti Putra Malaysia Press, 2013)
In today's world we can see numerous product inventions around us. Starting from intangible to tangible products, all of them are derived from human inventive and creative ideas. The invention of the airplane by the Wright Brothers in 1903 is a process of inventive and creative thinking that produced a new means of vehicle for human beings. This can be considered as the biggest breakthrough in the aviation history which provides an alternative transport that is time-saving, comfortable and convenient for the users.